Fake News and Radio Biafra between 1967 and 1970 in Nigeria: A Lesson for the Contemporary Media Industry in South-South Region - Chukwuemeka Orlu; Asor Confidence Asor (Researchparks Publishing, 2022)
The Nigerian State was entangled with civil unrest following months of political instability in Nigeria and the massacres of Igbo people in the northern part of the country during the summer of 1966. On 30 May 1967, the Eastern Region (Biafra) unilaterally declared its independence, sparking a civil war that, combined with a tight economic blockade of the secessionist region and the logistical support of foreign powers, lasted three years and claimed the lives of more than three million people. The fight between Nigerian and Biafran soldiers lasted from 6 July 1967 to 12 January 1970, when Biafra surrendered. Throughout the struggle, notably between 1968 and 1969, the media from across the globe descended to Nigeria to cover it for their readers, with varying degrees of success. Despite constraints, Radio Biafra was able to chronicle the progress on the ground, the growing humanitarian disaster and rising fatalities, the armaments race and the political landscape, and ultimately accomplished their goal of raising international attention to Nigeria. This study, based on Radio Biafra, critically assessed the prevalence of fake news with unreliable sources contributing to the confusion and a proliferation of unreliable pieces of news in the contemporary Nigeria and the lessons for media houses operating in the South-South region.